2009
DOI: 10.1590/s0103-90162009000200003
|View full text |Cite
|
Sign up to set email alerts
|

Nutritive value of sugarcane silage treated with chemical additives

Abstract: The use of ensiled sugarcane has been increased lately in Brazil due to the benefits that this technique represents. The objective of this study was to evaluate the effects of chemical additives on the nutritive value of sugarcane silages. The trial was carried out in a completely randomized experimental design with four replicates per treatment. The following additives were applied onto the fresh forage before ensiling: L. buchneri, lime or limestone, 1.0 and 1.5% (wet basis) each, and gypsum 1.0% (wet basis)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
15
1
12

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 11 publications
2
15
1
12
Order By: Relevance
“…Using 0.5% CaO, Balieiro Neto et al (2009) observed reduction of the NDF in relation to sugarcane silage without additive. The results found in this study corroborate the reports of Santos et al (2009), in research with sugarcane silages without additives or with chemical additive (1% or 1.5% CaO, 1% or 1.5% CaCO 3 , and 1% gypsum). Balieiro Neto et al (2009) found the highest NDF levels in silages without additives, and the lowest in silages with 1% CaO or 1.5% CaCO 3 .…”
supporting
confidence: 91%
“…Using 0.5% CaO, Balieiro Neto et al (2009) observed reduction of the NDF in relation to sugarcane silage without additive. The results found in this study corroborate the reports of Santos et al (2009), in research with sugarcane silages without additives or with chemical additive (1% or 1.5% CaO, 1% or 1.5% CaCO 3 , and 1% gypsum). Balieiro Neto et al (2009) found the highest NDF levels in silages without additives, and the lowest in silages with 1% CaO or 1.5% CaCO 3 .…”
supporting
confidence: 91%
“…De maneira similar, os teores de PB estão de acordo com os encontrados por Schmidt et al (2007) O teor de cinzas observado no tratamento controle apresentou valor inferior ao encontrado por Schmidt et al (2007). Por outro lado, Santos et al (2009), avaliando silagens de cana-de-açúcar aditivadas com cal virgem e calcário, encontraram valores de cinzas bem menores no momento da ensilagem (2,3% para a silagem controle e de 4,5 e 3,2% para as silagens contendo cal virgem ou calcário, respectivamente). Da mesma forma, neste trabalho, verificou-se aumento nos valores de cinzas quando o aditivo químico foi inserido no volumoso, o que possivelmente está relacionado ao fato de os aditivos serem de origem mineral e apresentarem grande proporção desta fração em sua totalidade.…”
Section: Resultsunclassified
“…O aumento na fração mineral da silagem controle, em relação aos valores da forragem antes da ensilagem, foi possivelmente ocasionado pela excessiva perda de componentes solúveis dessa silagem. Santos et al (2009) também verificou aumento no teor de cinzas em silagens de cana-de-açúcar tratadas com cal virgem e calcário. Na silagem com 1% de cal virgem, o autor encontrou valor de 6,1%, ao passo que, na silagem contendo 1% de calcário, constatou-se valor de 4,7% de cinzas.…”
Section: Resultsunclassified
See 2 more Smart Citations